Analisis Faktor penghambat perkembangan Ekonomi Kreatif Pada Destinasi Wisata Pantai Sengigi Kabupaten Lombok Barat - Asri Oktiani; Sri Maryanti; Faezal Faezal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the factors inhibiting the development of the creative economy in the Senggigi Beach Tourism Destination, West Lombok. The research is motivated by the declining competitiveness of the destination, limited innovation among creative economy actors, and increasing competition from emerging destinations such as the Mandalika Special Economic Zone. A descriptive qualitative method with a case study approach was employed. Data were collected through in-depth interviews, observations, and documentation involving 28 informants from various creative economy subsectors. Data analysis was conducted using a root cause analysis approach, including a Fishbone Diagram and thematic coding. The findings reveal that the main inhibiting factors originate internally, including low product innovation and differentiation, weak digital marketing, limited human resource competencies, and inadequate use of technology and business networks. External factors include the decline in tourist arrivals due to earthquakes and the pandemic, competition with modern destinations, shifting tourist preferences, and suboptimal government support. The interaction between these internal and external factors creates a stagnation cycle that hampers the growth of the creative economy in Senggigi. The study concludes that an integrated strategy is required, encompassing capacity building for creative actors, strengthening digital marketing, enhancing pentahelix collaboration, and repositioning Senggigi as a culture-based creative destination.